(NlIRIKA(B: [(NsTIHOTWORENIQ(B] /s (N~ASTX (B1s - (NlERMONTOW(B, (NmIHAIL `RXEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1976)
(NwA[EMU WNIMANI@ PREDSTAWLENA KNIGA(B, (NW KOTORU@ WO[LI LU^[IE OBRAZCY LIRIKI mIHAILA lERMONTOWA(B.s
rus
Keywords: (NpO\ZIQ(B, (NPO\MYs